Exploring Students’ Expectations and Motivations to Attend Secondary School in India - ROY, ANIRBAN; MOHAPATRA, ANIMESH KUMAR (INDIAN EDUCATIONAL REVIEW, 2025)
Academic promotion from lower to higher classes brings a copious amount of anxiety in addition to the joy of achievement among the school students. One of the primary concerns of the students is the gap between their (prior) expectations and the realities of the senior classes, which can inadvertently result in poor performance and taxing distress of the students. The current study aims to determine what expectations students carry while they begin Class X, considering the social importance bestowed on the Indian matriculation (Class X Board) examination. A survey-based analysis is done with the secondary students of Class X (n=237) from three schools—rural, semi-urban, urban—through 10-point rating scales, Likert items, and close-ended questions covering 31 statements of different expectations. The study identified various dimensions of expectations and motivations held by Class X students, which can be utilised to address context-specific challenges and enhance learning outcomes. Understanding these expectations is essential for designing targeted interventions that align with student needs and improve engagement. By integrating such insights into educational strategies, schools can create more supportive learning environments, ultimately contributing to better academic performance and holistic development of students.